Peran Perusahaan Multinasional Dalam Meningkatkan Sektor Perekonomian Di Indonesia - Nurfatmala Nurfatmala; Neneng Fitriah; Riska Komalasari; Sarip Hidayat; Fitri Raya (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2023)
Multinational corporations are involved in a country's economic sector because they are important in absorbing labor and increasing a country's per capita income. The purpose of this study is to highlight the importance of detailed knowledge about multinational companies that may have some impact on Indonesia's economy. The research method used is a qualitative research method using the technique of collecting library research data using multiple references and information from relevant institutions of the Indonesian economy. The findings show that the role of multinational corporations has both positive and negative impacts. On the positive side, the role of Multinationals could provide Indonesia with adequate opportunities to develop the country's economic sector through Indonesia's foreign exchange contributions. Apart from that, Indonesia is attracting attention from other countries as other countries believe that Indonesia can increase foreign investment due to Indonesia's rich resource potential and emphasis on labor wages in developing countries like Indonesia increasingly recognized. On the negative side, the Indonesian government does not emphasize multinational companies in terms of domestic trade and industry regulations, providing opportunities for domestic companies to compete domestically.